2021
DOI: 10.1111/jmft.12512
|View full text |Cite
|
Sign up to set email alerts
|

A call to action: Online learning and distance education in the training of couple and family therapists

Abstract: Distance education in couple and family therapy (CFT) has grown in recent years; however, due to the COVID‐19 pandemic, many CFT educators find themselves delivering emergency online education out of necessity and for the first time. Despite the growth of distance learning over the last decade, there is virtually no CFT scholarship on the topic. Comparable disciplines, including social work and professional counseling, are further along in researching distance learning. Outside of the counseling disciplines, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Accordingly, inconsistent training opportunities related to this mode of treatment delivery are observed. Despite the publication of TM-H-specific guidelines across professional organizations, suggesting that this is an accepted and widely utilized approach to delivering mental health treatment, many graduate programs do not formally train emerging mental health professionals in the provision of TM-H as a part of their standard curriculum (Harrison, 2021; Phillips et al, 2021; Pourmand et al, 2021). Of further note, there is a dearth of scholarly literature that explicitly outlines what specific knowledge and skills should be included in such training (Springer et al, 2020).…”
Section: Covid-19 In Rural Communitiesmentioning
confidence: 99%
“…Accordingly, inconsistent training opportunities related to this mode of treatment delivery are observed. Despite the publication of TM-H-specific guidelines across professional organizations, suggesting that this is an accepted and widely utilized approach to delivering mental health treatment, many graduate programs do not formally train emerging mental health professionals in the provision of TM-H as a part of their standard curriculum (Harrison, 2021; Phillips et al, 2021; Pourmand et al, 2021). Of further note, there is a dearth of scholarly literature that explicitly outlines what specific knowledge and skills should be included in such training (Springer et al, 2020).…”
Section: Covid-19 In Rural Communitiesmentioning
confidence: 99%
“…Specifically, this study seeks to better understand our online COAMFTE accredited MFT program’s faculty supervisors’ experiences with TS. To date there has been limited research on marriage and family therapy distance-education in general with recent calls to address this gap that exists in comparison to other mental health professions such as professional counseling and social work (Harrison, 2021 ). With TS being a key piece of distance-based MFT programs, this study also seeks to contribute to the literature on distance-based education in MFT.…”
Section: Intentionality In Telesupervision: a Phenomenological Study Of Academic Telesupervisionmentioning
confidence: 99%
“…While limited research exists on TS, what we know about the benefits and best practices of TS aligns with adult learning theory (e.g., Knowles, 1980 ) and research on distance-based education for mental health professionals (Snow et al, 2018 ). The MFT field has generated little research on distance-based education, yet we can draw from the findings of multiple studies produced by similar fields such as social work and counselor education (Harrison, 2021 ).…”
Section: Research On Telesupervisionmentioning
confidence: 99%
“…In tandem with this swift transition, the steady proliferation of online (50% or more of a program's curriculum is offered online) counseling programs had been a trend that started prior to the pandemic (Li & Su, 2021 ). The confluence of these two change processes—the forced, abrupt transition to remote learning and the incremental growth of online counseling programs—delineated the new landscape of counselors training (Harrison, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of computer‐mediated learning due to COVID‐19 further made it imperative to extend this line of inquiry. Despite the recent literature uptick of online learning in counseling, the journal articles are mainly conceptual in nature (e.g., Harrison, 2021 ; Wasik et al., 2019 ), studied through a qualitative lens (e.g., Bender & Werries, 2021 ; Holmes et al., 2020 ), or explored from counselor educators’ perspective (e.g., Hinkley et al., 2021 ). However, the broader education literature suggested that students’ perception of online learning plays a pivotal role in their learning outcomes, including motivation and persistence (Kauffman, 2015 ).…”
Section: Introductionmentioning
confidence: 99%